Infective Endocarditis: A Case with Prolonged Fever - Maulia Prismadani; Agus Subagjo (Universitas Airlangga, 2021)
Infective endocarditis (IE) is associated with a high rate of mortality and morbidity in patients with anomalies of heart valves. We present a case of a 23-year-old male known to have severe mitral regurgitation (MR) with a history of prolonged fever for 5 months. According to The Modified Duke Criteria, clinical sign and symptoms fulfilled one major criterion (echocardiography finding of vegetation on mitral valve) and three minor (fever of at least 380 Celsius, valvular heart disease as a predisposing heart condition, and positive blood culture for Lactococcus sp. and Pediococcus sp.) considered as definite IE. Fever is one of the most common symptoms of IE (>90% of cases). Patient with prolonged fever and structural abnormality of heart valve should be considered for acute or subacute of IE. Establishing an diagnosis of IE and appropriate antibiotic therapy will improve the patient's clinical condition, and reduce morbidity and mortality. Keywords: Infective endocarditis (IE), Prolonged fever